2016
DOI: 10.29052/ijehsr.v4.i3.2016.01-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Various Types of Viruses in Development of Early Aged Breast Cancer:A Brief Review

Abstract: World widely, Breast cancer is the most common type of cancer amongst women. External and internal factors both are responsible for beginning, advancement and development of breast cancer and from many studies it is well known that environmental elements have a significant effect in etiology of breast cancer. When it comes to environmental factors, effects of viruses are of great concern. Virus-associated cancer brings up a cancer in which the malicious conversion of the host's diseased cells results due to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 37 - 39 Wang et al showed that E7 elevates levels of c-Myc in murine C127 cells infected with bovine papillomavirus type 1 and E7 increases c-Myc binding to the hTERT promoter, E6 and E7 can increase transcription from TERT promoters in a synergistic manner. 40 , 41 Early protein 5 (E5) can affect receptor tyrosine kinases by associating with the cell membrane. HPV DNA has been reported to be found in human breast milk, indicating that the virus can certainly infect and accumulate in breast tissue, 42 , 43 while some studies 44 , 45 indicated that HPV DNA was not found in breast milk.…”
Section: Human Oncogenic Dna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 - 39 Wang et al showed that E7 elevates levels of c-Myc in murine C127 cells infected with bovine papillomavirus type 1 and E7 increases c-Myc binding to the hTERT promoter, E6 and E7 can increase transcription from TERT promoters in a synergistic manner. 40 , 41 Early protein 5 (E5) can affect receptor tyrosine kinases by associating with the cell membrane. HPV DNA has been reported to be found in human breast milk, indicating that the virus can certainly infect and accumulate in breast tissue, 42 , 43 while some studies 44 , 45 indicated that HPV DNA was not found in breast milk.…”
Section: Human Oncogenic Dna Virusesmentioning
confidence: 99%
“…Vaccines that prevent high risk HPVs consist of recombinant L1 proteins that form virus-like particles (VLPs). 40 , 41 Epidermodysplasia verruciformis is a hereditary disease infecting the skin linked to chronic HPV infection and also genetic predisposition play a part in cervical cancer. Anal cancer by HPV is more frequent in HIV-infected persons with immunodeficiency which increases the risk of high-grade cervical dysplasia and cancer.…”
Section: Human Oncogenic Dna Virusesmentioning
confidence: 99%